Biosynthesis of thyrotropin releasing hormone in the skin of Xenopus laevis: partial sequence of the precursor deduced from cloned cDNA. - Richter, K (1984)
Skin of Xenopus laevis contains relatively large quantities of thyrotropin releasing hormone (TRH). Total mRNA isolated from skin was cloned in the plasmid pUC8. Among 1400 cDNA clones, one was found with an insert of 478 nucleotides coding for the amino-terminal part of prepro-TRH. This clone was detected using a mixture of two synthetic undecanucleotides for colony hybridization. The single open reading frame starts with a methionine residue and a stretch of hydrophobic amino acids, as is typical for signal peptides, and terminates at the poly(C) tail without a stop codon. The deduced polypeptide of 123 amino acids contains three copies of the sequences Lys-Arg-Gln-His-Pro-Gly-Lys Arg-Arg and a fourth incomplete copy at the carboxyl end. Typical pro-hormone processing at this sequence would yield pGlu-His-Pro.NH2,i.e. TRH. It is concluded that the cloned part of the mRNA codes for prepro-TRH and that the TRH precursor from skin of X. laevis is a polyprotein containing at least four copies of the end product in its amino acid sequence.